PENGARUH PENYULUHAN DENGAN MEDIA TIGA DIMENSI DIORAMA TERHADAP PENGETAHUAN MENGGOSOK GIGI MURID SEKOLAH DASAR NEGERI 5 MENTENG PALANGKA RAYA - noorhafiji, noorhafiji; Astu Rahman, Waljuni; Isnawati, Isnawati; Sari, Emilda (JURNAL TERAPIS GIGI DAN MULUT, 2025)
One way to minimize the morbidity rate that occurs is through preventive measures carried out by promoting health since school age children. The results of the 2018 Central Kalimantan Riskesdas showed that the proportion of dental health problems was 42.58%. This study aims to determine whether there is an effect of counseling with three-dimensional diorama media on the knowledge of brushing teeth of students at State Elementary School 5 Menteng Palangka Raya. The method used is quasi-experimental research. With a one group pre-test post-test design approach. The population is all students of State Elementary School 5 Menteng Palangka Raya with a total of 113 people, the sample was taken by purposive sampling with the number of samples in this study being students aged 7-9 years, which is 42 people. The results of the Paired Sample T-test statistical test found a mean difference (average difference) of 3.14, with a known t-value of 18.995, the ρ value (probability value) of the test shows ρ = 0.000, so it is smaller than α 0.05 or (ρ = 0.000 <α 0.05). Based on the results of the study, it can be concluded that there is a significant influence of counseling using three-dimensional diorama media on knowledge of brushing teeth at State Elementary School 5 Menteng Palangka Raya, Central Kalimantan Province